Resilience level in health personnel facing the Covid-19 pandemic - Gamboa-Moreno, Linda Noheli (2021)
Background: Resilience is a determining factor in helping to cope with any stressful situation, therefore the objective of our study was to measure the resilience level in health personnel facing the COVID-19 pandemic at two hospitals in the city of Trujillo. The study: A cross-sectional descriptive study was carried out with 106 health workers, who were administered a questionnaire consisting of 25 items through an interview. Findings: It was found that the majority of participants were female (67.9% vs 32.1%) and 40.6%, medical personnel. Conclusions: The health personnel presented a high resilience level facing the Covid-19 pandemic.